Informal Employment, the Tertiary Sector, and the Gross Domestic Product: A Structural Equations Model for the Mexican Economy - David Robles Ortiz; Raymundo Alexei Ambriz Torres (Economies, 2024)
In Mexico, approximately 55% of the working population is employed informally, contributing 24.4% to the Gross Domestic Product (GDP) in 2022. This study analyzed the impact of wages, taxes, government spending, and unemployment on the informal economy of Mexico from 1980 to 2022, as well as its relationship with the tertiary sector’s contribution to the GDP. The methodology of the study was structural equation modeling. The findings of this study revealed that an increase in taxes, the unemployment rate, and the minimum wage in Mexico tends to be accompanied by a rise in informal employment. Finally, a unitary change in the latent variable informality affected the growth of the tertiary sector’s contribution to the GDP by 0.37 units.